Pesticide exposure among Czech adults and children from the CELSPAC-SPECIMEn cohort: Urinary biomarker levels and associated health risks - Šulc, Libor; Janoš, Tomáš; Figueiredo, Daniel; Ottenbros, Ilse; Šenk, Petr; Mikeš, Ondřej; Huss, Anke; Čupr, Pavel (Environmental research, 2022)
Current-use pesticides (CUP) are extensively applied in both agricultural and urban settings. Exposure occurs mainly via the dietary pathway; however, other pathways such as inhalation or skin contact are also important. In this study, urinary levels of 12 CUP metabolites were investigated among 110 parent-child pairs during two seasons of 2020. Metabolites of pyrethroids (3-PBA, t/c-DCCA), chlorpyrifos (TCPY), and tebuconazole (TEB-OH) were detected in more than 60% of the samples. Chlorpyrifos metabolite was found at the highest concentration and tebuconazole was detected in almost all samples. CUP urinary metabolite levels were significantly higher in children in comparison to adults, except for tebuconazole, which was similar in both groups. In children, winter samples had significantly higher concentrations of pyrethroid and chlorpyrifos metabolites in comparison to the summer samples, but in adults, only chlorpyrifos metabolite concentrations were higher in the winter. No association between CUP urinary metabolite levels and proximity/surface of agricultural areas around residences was observed. Based on our findings, we suspect that CUP exposure is mainly driven by diet and that the effect of environmental exposure is less significant. Daily Intakes were estimated with three possible scenarios considering the amount of the metabolite excreted in urine and were compared to Acceptable Daily Intake values. Using a realistic scenario, exposure to chlorpyrifos exhibited the highest health risk, but still within a safe level. The Acceptable Daily Intake was exceeded only in one child in the case of cypermethrin. The cumulative risk assessment of pesticide mixtures having an effect on the nervous system, based on the total margin of exposure calculations, did not indicate any risk. The overall risk associated with pesticide exposure in the observed population was low. However, the risk observed using the worst-case scenario suggests the need for continuous evaluation of human exposure to such compounds, especially in children.
Keywords: Cumulative risk assessment; pesticidy; Humans; insekticidy; vystavení vlivu životního prostředí; dospělí; pyrethriny; lidé; Biomarkers; Chlorpyrifos; Insecticides; Pyrethrins; Pesticides; Adult; Urine; biologické markery; Czech Republic; dursban; Environmental Exposure; Pyrethroids; Tebuconazole; Česká republika; HBM4EU